2016
DOI: 10.1186/s40249-016-0186-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and paraclinical profile, and predictors of outcome in 90 cases of scrub typhus, Meghalaya, India

Abstract: BackgroundIndia is an integral component of “tsutsugamushi triangle” which depicts a part of the globe endemic to scrub typhus. Owing to frequent outbreaks witnessed in different parts of the country in the recent past, scrub typhus is described as a re-emerging infectious disease in India. The present study aimed to study the clinical and paraclinical profile, complications and predictors of outcome among 90 cases of scrub typhus diagnosed in a hospital of north-eastern India from Sept 2011 to Aug 2012.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 42 publications
(48 reference statements)
5
39
2
Order By: Relevance
“…Additionally, the widespread use of Orientia- resistant beta-lactam antimicrobials coincided with the increased incidences of scrub typhus [ 101 ]. In this review, we have documented human outbreaks of scrub typhus from 2007 to the present, 2017 ( Table 1 ) [ 19 , 95 , 99 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 ].…”
Section: Scrub Typhus Outbreaksmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, the widespread use of Orientia- resistant beta-lactam antimicrobials coincided with the increased incidences of scrub typhus [ 101 ]. In this review, we have documented human outbreaks of scrub typhus from 2007 to the present, 2017 ( Table 1 ) [ 19 , 95 , 99 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 ].…”
Section: Scrub Typhus Outbreaksmentioning
confidence: 99%
“…The baseline level of scrub typhus in the endemic regions may not be known, and therefore, some of the scrub typhus outbreaks described herein may be sporadic, unrelated cases of the same disease, particularly for the hospital-based studies conducted prospectively [ 121 ] or retrospectively [ 114 , 116 ]. In these outbreaks, the patients presented with an undifferentiated febrile illness of varying severity with symptoms ranging from fever, headache, cough, rash and/or eschar, myalgia, lymphadenopathy [ 19 , 108 ], to more dramatic ones such as multiple organ failure [ 95 , 109 ], and death in some of the outbreaks [ 95 , 104 , 105 , 114 , 115 , 116 ]. In a review by Taylor et al, it was observed that the case fatality rate can be as high as 30–70% in untreated cases [ 96 ].…”
Section: Scrub Typhus Outbreaksmentioning
confidence: 99%
See 2 more Smart Citations
“…Scrub typhus in India is considered as the emerging and re‐emerging infectious disease . Outbreaks of this disease were also reported in various Indian provinces . The previous report showed that the infection can lead to acute encephalitis syndrome, Parkinson's disease, and various neurological complications …”
Section: Introductionmentioning
confidence: 94%